PENGARUH PENGGUNAAN PPT INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI BAGIAN-BAGIAN TUMBUHAN: Penelitian Tindakan Kelas - Denny Setyadi; Etna Weka Sari; Jahwa Hayatun Nufuz; Muhammad Fathan Noor Habibie; M. Ihsan; Ahmad Suriansyah; Maimunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted using a quasi-experimental method with a Nonequivalent Control Group Design, involving 14 students divided into two groups: the experimental group, which was taught using interactive PowerPoint media, and the control group, which was taught using the lecture method. Data were collected through a multiple-choice test consisting of 10 questions administered before (pretest) and after (posttest) the treatment. Data analysis was carried out using normality, homogeneity, and independent samples t-test. The results showed that the average posttest score of the experimental group increased from 48.6 to 67.1, while the control group remained at 31.4. The t-test revealed a significant difference (p < 0.05), indicating that the use of interactive PowerPoint media is more effective than the lecture method in improving elementary school students’ science learning outcomes.